Between‐Individual Differences in Baseline Well‐Being and Emotion Regulation Strategy Use Moderate the Effect of a Self‐Help Cognitive‐Behavioral Intervention for Typical Adults. Issue 2 (23rd December 2019) - Pavani, Jean‐Baptiste; Berna, Guillaume; Andreotti, Eva; Guiller, Theo; Antoine, Pascal; Dauvier, Bruno; Congard, Anne
Abstract : Background: Self‐help interventions intended to help nonclinical individuals regulate their emotions can have important social benefits (i.e. mental disorder prevention, well‐being promotion). However, their mean effect size on well‐being is generally low, possibly because there are considerable between‐individual differences in the response to these interventions. The present study examined whether individuals' baseline levels of emotional well‐being and engagement in emotion regulation strategies moderate the effects on these same variables in a 4‐week self‐help cognitive‐behavioral intervention intended for typical adults. Methods: Data were collected from 158 nonclinical French adults ( n = 95 for the control group, n = 63 for the cognitive‐behavioral group) using experience sampling. Emotional well‐being was assessed, as well as the engagement in three emotion regulation strategies (i.e. cognitive reappraisal, problem solving, and appreciation). Results: As expected, the post‐test scores on some variables were significantly predicted by the interactions between the intervention and the pre‐test scores on these same variables. In particular, it was the participants with the most negative baseline levels (i.e. low emotional well‐being, low engagement in appreciation) who benefitted most from the intervention. Conclusions: Results are discussed in the light of current knowledge on between‐individual differences in how individuals respond to interventions.